Primary Cutaneous Gamma-Delta (γ/δ) T-cell Lymphoma: An Unusual Case With Very Subtle Histopathological Findings. (October 2016) - Ramani, Nisha S.; Curry, Jonathan L.; Merrill, E. Dean; Aung, Phyu P.; Prieto, Victor; Tetzlaff, Michael T.; Duvic, Madeleine; Miranda, Roberto; Torres-Cabala, Carlos
Abstract : Abstract: Primary cutaneous γ/δ T-cell lymphoma (PCGDTCL) accounts for <1% of all primary cutaneous lymphomas. These rare diseases are believed to originate from γ/δ lymphocytes. Clinical presentation may vary, but its clinical behavior is regarded as aggressive and long-term survival is anecdotal. This study describes the case of a 60-year-old man with multiple, rapidly progressing skin plaques on his head, arms, torso, buttocks, and legs. The histopathological changes seen in the skin biopsy were extraordinarily subtle with mild epidermal hyperplasia and a very sparse lymphoid infiltrate involving epidermis and superficial dermis. Immunohistochemical studies revealed the atypical intraepidermal hyperchromatic cells to be mostly positive for CD3 and CD7 and negative for both CD4 and CD8. The intraepidermal atypical lymphocytes were positive for TCR gamma, and negative for betaF1 and CD56. The clinical, morphologic, and immunohistochemical findings supported the diagnosis of PCGDTCL. This case illustrates a case of epidermotropic variant of PCGDTCL that, albeit a bland histopathological presentation, was associated with an aggressive clinical behavior.